PEMANFAATAN FUNGSI MUSEUM SEBAGAI SUMBER BELAJAR SEJARAH DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS - Evitasari, Okta; Qodariah, Lelly; Gunawan, Rudy (Universitas Indraprasta PGRI, 2020)
This research uses a descriptive qualitative method with a case study approach where the researcher searches and collects resources in the form of informationand data about the use of museums as a source of historical learning, which inturn provides descriptive data in the form of words, writing of objects observedby researchers. The data used in this study comes from sources, places (museum buildings and collections) and documents. Data collection techniques used in this study were interviews, observation and document analysis. In this study, researchers used source triangle measurement by searching data through more than one informant related to the use of the museum's role as a source of historical learning. The results showed that the museum can motivate students and make students easy in the learning history process. The visit to the museum is something that deserves to be considered as a source of visual learning forstudents. A visit to the history object is expected to change the assumption thatstudents studying history are not boring and satiating, but something interestingand fun. On the basis of the findings in the field of SMA Negeri 5 Depok, the useof the museum as a learning source is indeed not yet optimal, due to variousfactors such as the lack of broad socialization to schools and the limited reach ofthe museum, which is an obstacle to National Awakening Museum in an effort tomake the museum as a means to study history.Keywords: learning materials, students, museums